2011
DOI: 10.1096/fj.11-195792
|View full text |Cite
|
Sign up to set email alerts
|

The cysteinyl leukotriene 2 receptor mediates retinal edema and pathological neovascularization in a murine model of oxygen‐induced retinopathy

Abstract: Leukotrienes have been implicated in the pathogenesis of degenerative diabetic retinopathy, with research focusing primarily on leukotriene B(4), with little attention devoted to the cysteinyl leukotrienes (cysLTs), which act through cysLT receptors (CysLT(1)R and CysLT(2)R). We demonstrate here the presence of CysLT(2)R in pericytes and endothelial cells of superficial retinal vasculature using an indirect assay by assessment of β-galactosidase expression in CysLT(2)R-knockout (KO) mice. Retinal damage was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…This may be due to the drug targeting one specific CysLT receptor at lower concentrations and more than one CysLT receptor at higher concentrations. In agreement, Barajas-Espinosa et al (37) reported a similar finding when Cyslt2r knockout mice were exposed to the OIR experimental paradigm. P17 flat-mount retinas, the same time point analyzed in our study, exhibited both reduced revascularization and increased neovascularization.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This may be due to the drug targeting one specific CysLT receptor at lower concentrations and more than one CysLT receptor at higher concentrations. In agreement, Barajas-Espinosa et al (37) reported a similar finding when Cyslt2r knockout mice were exposed to the OIR experimental paradigm. P17 flat-mount retinas, the same time point analyzed in our study, exhibited both reduced revascularization and increased neovascularization.…”
Section: Discussionsupporting
confidence: 80%
“…5B). Previous studies have confirmed retinal expression of CysLT 1 in rodent models of retinal neovascularization (37), and we demonstrated here ocular expression of the zebrafish cysltr1 and cysltr2 genes during hyaloid vessel development (Fig. 5D) and expression of cysteinyl leukotriene receptors 1 and 2 in human endothelial cells (HMEC-1), human retinal microvascular endothelial cells (ACBRI-181), and human RPE cells (ARPE-19) (Fig.…”
Section: G-i)supporting
confidence: 83%
See 3 more Smart Citations